Determination of new grade and strength of steel bars for non-welded reinforced concrete structures with high carbon content - Ju Su In; Kim Sok Bong; Mun Song Hyok (Talenta Publisher, 2026)
In the modern development of reinforced concrete structures is not intended to use low carbon steel as reinforcement, so that the connection of steel bars is the welded joint, and the connection by sleeve, bushing and binding wire is the main one. International Organization (ISO) and some countries have standardized reinforcement mainly for non-welded reinforced concrete structures, and therefore, carbon content is not specified in the chemical element content regulations. Therefore, we have developed and adopted a new grade for steel bars with carbon content ranging from 0.25 to 0.37, and determined their standard strength and computational strength to be applicable to the design of reinforced concrete structures.